Optimization of the Internal Quality Audit Process Through the Development of an Integrated Information System - Febri Sarif Hidayat; Khalimaturofi’ah; Heni Rahmawati (Jurnal Ilmiah Informatika dan Komputer, 2025)
The Internal Quality Audit (IQA) process is a crucial element for maintaining the quality of higher education. However, its implementation at STIMIK Tunas Bangsa Banjarnegara faces challenges, particularly with manual documentation. The use of paper-based forms, decentralized recording of findings, and separate reports often cause delays, data duplication, and difficulty in tracking follow-up actions. This research aims to develop an integrated information system to optimize the IQA process and improve the ease of documentation up to the findings report stage. This study uses a qualitative approach with a case study design. Data was collected through observation to understand the manual workflow and interviews with relevant parties to gather system requirements. The system was developed using the Prototype method and built with the PHP programming language and a MySQL database. The research resulted in a system named SIMATIKA (Sistem Audit Mutu Internal Kampus), all of whose features function well based on BlackBox Testing. These features include audit period management, indicator management, user configuration, and audit assignment. The system also received a score of 86% from a user questionnaire, indicating very good feasibility and acceptance. Thus, SIMATIKA successfully optimizes the IQA process at the campus.